Pemberdayaan UMKM Melalaui Pendekatan Asset-Based Community Development dan Digital Marketing di Desa Sugihan: Empowering MSMEs through an Asset-Based Community Development Approach and Digital Marketing in Sugihan Village - Khamdani, Muhamad; Sagita, Diah Mutiara; Himmatus Sa'diyah, Nelly; 'Aini, Wirdatul; Rahayu, Sella Fajar; Masruri, Dava Lazuardy (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
Abstract Consumer behavior tendencies that depend on digital platforms require MSMEs to undergo digital transformation to remain competitive. The lack of digital literacy is a significant issue in digital transformation, necessitating knowledge transfer through socialization, training, and mentoring to ensure the program's sustainability. The Asset-Based Community Development (ABCD) approach used in this research goes through five stages, namely identifying community potential, formulating a shared vision, designing and implementing digital marketing strategies, and monitoring program sustainability. The results show an increase in digital literacy capacity among MSME actors with the ability to operate various digital platforms. The synergy between students, village governments, and local communities has proven to be the key to the success and sustainability of the program. This emphasizes that MSME development should be based on a combination of education, practical experience, and ongoing mentorship. Thus, this program can serve as a model for the development of MSMEs as well as tangible evidence of community service in creating independent, adaptive, and sustainable competitive MSMEs. Keywords: Empowerment, MSMEs, ABCD approach, digital marketing Abstrak Kecenderungan perilaku konsumen yang bergantung pada platform digital menuntut UMKM melakukan transformasi digital agar tetap kompetitif. Minimnya literasi digital menjadi masalah utama dalam transformasi digital, sehingga memerlukan transfer pengetahuan dalam bentuk sosialisasi, pelatihan, dan pendampingan untuk memastikan keberlanjutan program. Pendekatan Asset-Based Community Development (ABCD) yang digunakan dalam penelitian ini melalui lima tahap, yakni identifikasi potensi komunitas, perumusan visi bersama, perancangan dan pelaksanaan strategi pemasaran digital, serta monitoring keberlanjutan program. Hasil penelitian menunjukkan peningkatan kapasitas literasi digital pelaku UMKM dengan kemampuan mengoperasikan beragam platform digital. Sinergi antara mahasiswa, pemerintah desa, dan komunitas lokal terbukti menjadi kunci keberhasilan dan keberlanjutan program. Hal ini menegaskan bahwa pengembangan UMKM harus berlandaskan pada kombinasi edukasi, praktik, dan pendampingan berkelanjutan. Dengan demikian, program ini dapat dijadikan model bagi pengembangan UMKM, sekaligus bukti nyata pengabdian masyarakat dalam mencetak UMKM yang mandiri, adaptif, dan berdaya saing berkelanjutan. Kata kunci: Pemberdayaan, UMKM, pendekatan ABCD, digital marketing